Sympathetic function and markers of inflammation in well-controlled HIV - Jessica Robinson-Papp; Varuna Astha; Alexandra Nmashie; Sandeep K. Sharma; Seunghee Kim-Schulze; Jacinta Murray; Mary Catherine George; Susan Morgello; Bridget R. Mueller; Steven A. Lawrence; Emma K.T. Benn (Brain, Behavior, & Immunity - Health, 2020)
Purpose: HIV-associated autonomic neuropathy (HIV-AN) is common and may be associated with both sympathetic and parasympathetic dysfunction. Sympathetic nervous system (SNS) dysfunction occurs on a continuum of hyper-to hypo-adrenergic function, and may be a mediator between psychological stress and chronic inflammation. We sought to describe patterns of SNS dysfunction in people living with HIV, and to determine whether SNS dysfunction is associated with markers of systemic inflammation (focusing on IL-6 and TNF-α) and pain and anxiety. Methods: Forty-seven people with well-controlled HIV and without confounding medical conditions or medications completed the Medical Outcomes Survey (MOS-HIV), quantification of a panel of 41 plasma cytokines/chemokines, and a standardized, non-invasive autonomic reflex screen (ARS). Adrenergic baroreflex sensitivity (BRSA) was calculated from the ARS as a measure of SNS function. Results: Pain (46%) and anxiety (52%) were commonly reported on the MOS-HIV. BRSA was reduced in 30% of participants and elevated in 9% with the latter occurring only in participants with normal to mild HIV-AN. BRSA was significantly associated with IL-6, but not with TNF-α, pain or anxiety. Exploratory analyses also revealed positive associations of BRSA with numerous other cytokines with no significant inverse associations. Conclusion: Higher BRSA, indicative of a more hyperadrenergic state, can be part of the spectrum of early HIV-AN, and may be associated with elevations in multiple cytokines including IL-6. These associations do not appear to be driven by stressors such as pain or anxiety.